Roles of VMP1 in Autophagy and ER–Membrane Contact: Potential Implications in Neurodegenerative Disorders - Wang, Panpan; Kou, Daqing; Le, Weidong (Frontiers in Molecular Neuroscience, 2020)
Cellular communication processes are highly dynamic and mediated, at least in part, by contacts between various membrane structures. The endoplasmic reticulum (ER), the major biosynthetic organelle of the cell, establishes an extensive network with other membrane structures to regulate the transport of intracellular molecules. Vacuole membrane protein 1 (VMP1), an ER-localized metazoan-specific protein, plays important roles in the formation of autophagosomes and communication between the ER and other organelles, including mitochondria, autophagosome precursor membranes, Golgi, lipid droplets, and endosomes. Increasing evidence has indicated that autophagy and ER-membrane communication at membrane contact sites are closely related to neurodegenerative disorders, such as Parkinson’s disease, Alzheimer's disease, and amyotrophic lateral sclerosis. In this review, we summarize the roles of VMP1 in autophagy and ER membrane contacts, and discuss their potential implications for neurodegenerative diseases.